P288 Is there any value of preoperative small bowel evaluation in patients with ulcerative colitis about to undergo ileal pouch-anal anastomosis?. (25th January 2019) - Truong, A; Fernandez, K; Zaghiyan, K; Fleshner, P
Abstract: Background: Ileal pouch-anal anastomosis (IPAA) is the standard operative approach to ulcerative colitis (UC) patients requiring surgery for medically refractory disease or dysplasia. Despite excellent long-term outcomes, pouchitis or de novo Crohn's disease (CD) are adverse outcomes that occur frequently after IPAA. Little is known regarding the utility of small bowel evaluation (SBE) before IPAA. The aim of this study was to assess the value of preoperative SBE in predicting adverse outcomes in UC patients undergoing IPAA. Methods: Consecutive UC patients undergoing IPAA between 2000 and 2017 were identified. SBE included endoluminal imaging via wireless capsule endoscopy (WCE) or radiographic imaging via small bowel follow through (SBFT), magnetic resonance enterography (MRE), or computed tomography enterography (CTE). Abnormal preoperative imaging alone without other clinical manifestations was not sufficient for the diagnosis of CD or inflammatory bowel disease unclassified (IBDU), both of which were excluded. Adverse outcomes were assessed prospectively and included no pouchitis (NP), acute pouchitis (AP; antibiotic responsive), chronic pouchitis (CP; antibiotic dependent/resistant) or de novo CD (five or more mucosal ulcers proximal to the ileal pouch or perianal complication 3 months after ileostomy closure). Results: Of the 328 study patients, 190 (58%) had preoperative SBE and 138 (42%) had no preoperative SBE. Preoperative SBE included WCE ( n = 72), SBFT ( n = 64), CTE/MRE ( n = 54). Only 19 (10%) patients with preoperative SBE had an abnormal study. Clinical and disease characteristics were not statistically different between patient groups with or without preoperative SBE. After a median follow-up of 41 (range 3–260) months, outcomes included AP ( n = 58; 18%), CP ( n = 27; 8%) and de novo CD ( n = 50; 15%). There was no significant difference in AP, CP, or de novo CD between patient groups with or without preoperative SBE ( p = 0.17). Additionally, there were no significant associations between any abnormal preoperative SBE study and the incidence of AP, CP and de novo CD ( p = 0.19). Figure 1. Adverse pouch outcomes by imaging result. Nml: normal, Abn: abnormal, WCE: wireless capsule endoscopy, SBFT: small bowel follow through, CT/MRE: computed tomography/magnetic resonance enterography, SBE: small bowel evaluation. All p > 0.05. Conclusions: In this largest to date prospective series investigating the value of preoperative SBE in UC, only 10% of patients had an abnormal study. Outcomes of IPAA were not significantly different between UC patients with or without preoperative SBE, nor were they different between patients with abnormal and normal preoperative SBE. Taken together, there appears to be little value in performing preoperative SBE in UC patients about to undergo IPAA.